Penyakit Moyamoya Tahap III menurut Klasifikasi Suzuki pada Orang Dewasa: Diagnosis dan Penatalaksanaan Konservatif — Laporan Kasus: Laporan Kasus - Candrayuni, Ni Made Ayu; Riyadi, Marsya Julia; Wardhana, I Made Edwin Alberty (PT Kalbe Farma Tbk., 2026)
Introduction: Moyamoya disease (MMD) is a rare, progressive cerebrovascular condition, predisposing patients to ischemic or hemorrhagic strokes—particularly among Asian populations. Case: A 38-year-old male with a prior ischemic stroke in 2023 presented with acute left lower limb weakness lasting two days. MRI showed an acute and chronic ischemic lesion, and an acute lacunar infarct in the right superior frontal gyrus. MRA and cerebral angiography confirmed Suzuki stage III MMD, with A1 right anterior cerebral artery (ACA) occlusion and collateral flow from the left posterior cerebral artery (PCA). Cerebral angiography revealed occlusion of the proximal A1 segment of the right ACA and a characteristic “puff of smoke” appearance from abnormal collateral vessels in the distal branches of the right middle cerebral artery (MCA). The patient was managed conservatively with cilostazol, rosuvastatin, and antiplatelet therapy, alongside physical rehabilitation, resulting in functional improvement. Discussion: MMD is a progressive vasculopathy that may cause recurrent cerebrovascular events due to impaired cerebral perfusion. Cerebral angiography remains essential for diagnosis and Suzuki staging. Although revascularization surgery is the standard treatment to improve cerebral blood flow and reduce stroke risk, conservative management may be considered in selected patients based on clinical stability, collateral circulation, and treatment indications. In this case, conservative therapy combined with rehabilitation was associated with clinical improvement, although continuous monitoring is required due to the progressive nature of the disease. Conclusion: Early diagnosis of MMD through advanced neuroimaging is crucial for preventing recurrent stroke and guiding treatment decisions. This case highlights that individualized conservative management may provide clinical benefits in adult Suzuki stage III MMD when surgical intervention is not immediately performed, while long-term follow-up remains essential.